SemiActive Suspension Control Design for Vehicles - Savaresi, S. M. (Butterworth–Heinemann, 2012)
Semi-Active Suspension Control Design for Vehicles provides a comprehensive overview of semi-active suspension systems with an emphasis on performance analysis and control design. Several different approaches using different control theories are presented and evaluated in the book, with methodology provided to analyze and evaluate suspension performances while identifying optimal performance bounds